2018
DOI: 10.2196/resprot.7937
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Preliminary Effectiveness of the Homework Intervention Strategy (eHIS) Program to Enhance Male Condom Use: Research Protocol

Abstract: BackgroundAlthough condoms are effective in reducing the risk of sexually transmitted infections (STIs) and unintended pregnancy, they are still often not used consistently and correctly. Negative impact on sensation and pleasure, ruining the mood, causing problems with maintaining erection, and condom slippage or breakage are some of the reasons given by men explaining why they do not want to use condoms. Although many interventions promoting condom use exist, some of them delivered online are complex and tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…The trial is delivered using Lifeguide , an interactive web-based intervention software platform and secure validated data management system designed to collect participant information and deliver digital interventions to support health behavior change [ 23 , 26 ]. The Lifeguide platform can be accessed via any internet-enabled device, and recruitment sites are provided with handheld tablet computers for recruitment purposes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The trial is delivered using Lifeguide , an interactive web-based intervention software platform and secure validated data management system designed to collect participant information and deliver digital interventions to support health behavior change [ 23 , 26 ]. The Lifeguide platform can be accessed via any internet-enabled device, and recruitment sites are provided with handheld tablet computers for recruitment purposes.…”
Section: Methodsmentioning
confidence: 99%
“…Our trial is powered to detect a 45% reduction in chlamydia test positivity among our intervention arms—from 11% to 6% at 6 months after randomization. Previous piloting suggests that the intervention is likely to be equally effective across all stratification subgroups (deprivation, ethnicity, sexual orientation, and age) [ 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The trial was designed to detect a reduction in positivity rates from 11% (observed among men aged 15-24 years in national screening [33]) to 6% at six months post randomisation. Based on pilot data suggesting equal intervention effectiveness across subgroups (deprivation, ethnicity, sexual orientation, age) and aiming for 85% power and assuming 36% attrition (observed in feasibility testing), the trial targeted 2231 participants across all arms (G*Power 3.1.9.2) [24,25,34]. Progression criteria were established for recruitment, uptake of STI screening and follow-up attrition [27].…”
Section: Sample Sizementioning
confidence: 99%
“…Development of the HIS-UK intervention was guided by the Information-Motivation-Behavioural Skills (IMBS) theoretical model of behaviour change which has been shown to be effective with young people [21,22]. In HIS-UK the impetus for change comes from the promotion of solitary experimentation with different condom and lubricant types and a focus on pleasure [23][24][25][26].…”
mentioning
confidence: 99%